Money, islamic banks and the real economy - Abdul Ghafar Ismail (Cengage Learning Asia Pte Ltd. (Malaysia Branch), 2018)
This book is intended to develop some important discourses on three important subjects, that is, money, Islamic banks and the real economy. The discussion on money will highlight the role of money as capital and medium of exchange. It starts with an understanding of why money is so important to the smooth functioning of the economy and how it improves human wellbeing, we need to understand exactly what money is. To quantify the impact of money on the economy, we need to be able to measure it. The goals of these discussions is to understand what the concept of money is, how we use it, how we measure it and how we channel it to Islamic banking. The discourse on Islamic banks will focus on the management of Islamic banks' funds. After completing this, we should be able to: explain the composition of a typical Islamic bank's balance sheet and the interrelationships between its accounts, including assets, liabilities and owners' equity; note the use and important of call reports, and state why balance sheets must be accurate and timely. In this discourse, we also examine how regulators regulate and supervise Islamic banking operations. Finally, the link between money, Islamic banks and the real economy will become the third discourse of this book. The contribution of the Islamic banking industry to the current economic order is based upon a renewed application of Islamic law (or the Shariah), in modern economic and financial transactions. These measures must be seen as integral to developing the Islamic ideals of society and economy, based on the Islamic principles of social justice and humanity